Safety and feasibility of left atrial appendage inversion in swine: A proof-of-concept study for potential therapy to prevent embolic stroke - Wang, Yanmin; Wang, Mengjun; Guo, Xiaomei; Han, Ling; Kassab, Ghassan (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Left atrial appendage (LAA) occlusion or exclusion has been used in patients with atrial fibrillation to prevent stroke, but the techniques and devices have shortcomings. This study aims to validate the safety and feasibility of a novel LAA inversion procedure. Methods: LAA inversion procedures were done in six pigs. Before the procedure and at 8 weeks postoperatively, heart rate, blood pressure, and electrocardiogram (ECG) were recorded. The serum concentration of atrial natriuretic peptide (ANP) was measured. The LAA was observed and measured by transesophageal echocardiogram (TEE) and intracardiac echocardiogram (ICE). At 8 weeks after LAA inversion, the animal was euthanized. The heart was collected for morphology and histology, including hematoxylin-eosin, Masson trichrome, and immunofluorescence staining. Results: TEE and ICE showed that LAA was inverted, and the inversion was maintained during the 8-week study duration. Food intake, body weight gain, heart rate, blood pressure, ECG, and serum ANP level were comparable before and after the procedure. Morphology and histological staining showed that there was no obvious inflammation or thrombus. Tissue remodeling and fibrosis were observed at the LAA inverted site. Conclusion: The inversion of LAA effectively eliminates the dead space of LAA and thus may reduce the risk of embolic stroke. The novel procedure is safe and feasible, but the efficacy in reducing embolization remains to be demonstrated in future studies.